Molecular chemistry approaches for tuning the properties of two-dimensional transition metal dichalcogenides - Bertolazzi, Simone; Backes, Claudia (Chemical Society reviews, 2018)
Two-dimensional (2D) semiconductors, such as ultrathin layers of transition metal dichalcogenides (TMDs), offer a unique combination of electronic, optical and mechanical properties, and hold potential to enable a host of new device applications spanning from flexible/wearable (opto)electronics to energy-harvesting and sensing technologies. A critical requirement for developing practical and reliable electronic devices based on semiconducting TMDs consists in achieving a full control over their charge-carrier polarity and doping. Inconveniently, such a challenging task cannot be accomplished by means of well-established doping techniques (e.g. ion implantation and diffusion), which unavoidably damage the 2D crystals resulting in degraded device performances. Nowadays, a number of alternatives are being investigated, including various (supra)molecular chemistry approaches relying on the combination of 2D semiconductors with electroactive donor/acceptor molecules. As yet, a large variety of molecular systems have been utilized for functionalizing 2D TMDs via both covalent and non-covalent interactions. Such research endeavours enabled not only the tuning of the charge-carrier doping but also the engineering of the optical, electronic, magnetic, thermal and sensing properties of semiconducting TMDs for specific device applications. Here, we will review the most enlightening recent advancements in experimental (supra)molecular chemistry methods for tailoring the properties of atomically-thin TMDs – in the form of substrate-supported or solution-dispersed nanosheets – and we will discuss the opportunities and the challenges towards the realization of novel hybrid materials and devices based on 2D semiconductors and molecular systems.